RESEARCH OF THE VARIABILITY OF A BOOTIS STARS BY USING THE DUAL CHANNEL PHOTOMETER - Dorokhova, T. N.; Dorokhov, N. I. (Одеські астрономічні публікації, 2017)
3 bona fide A Boo stars were observed by using the dual-channel photometer at the Mt. Dushak-Erekdag observational station. Two peaks at frequencies f1 = 15.85c/d and f2 = 27.54c/d were revealed in the amplitude Fourier spectrum of HD 221756, HD 204041 and HD 38545 proved to be constant. Probably, comparison star HD 204121 has low amplitude variability.